2016
DOI: 10.1002/zamm.201500219
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of a circular inhomogeneity with homogeneously imperfect interface in plane micropolar elasticity

Abstract: In this paper we derive the full analytical solution for the problem of a circular micropolar inhomogeneity in an infinite micropolar plate subjected to a remote uni‐axial tension. The interface between the inhomogeneity and the surrounding matrix is considered to be homogeneously imperfect. This model has been well known in classical elasticity and was validated experimentally and verified analytically . Mathematically it is expressed in the assumption that the stresses are continuous across the interface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It can be shown that these assumptions are possible if and only if φ 1 = φ 2 =0 everywhere in both the interior and exterior domains so the problem reduces to the classical one considered in the work by Shen et al [16]. The interface condition given by equation (29) with 3 interface parameters is supported by Videla and Atroshchenko [31] where a circular inclusion under the assumptions of plane micropolar elasticity is considered.…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that these assumptions are possible if and only if φ 1 = φ 2 =0 everywhere in both the interior and exterior domains so the problem reduces to the classical one considered in the work by Shen et al [16]. The interface condition given by equation (29) with 3 interface parameters is supported by Videla and Atroshchenko [31] where a circular inclusion under the assumptions of plane micropolar elasticity is considered.…”
Section: Examplementioning
confidence: 99%
“…with 3 interface parameters is supported by Videla and Atroshchenko[31] where a circular inclusion under the assumptions of plane micropolar elasticity is considered.Consider an inclusion represented by an ellipse prescribed by the equationsx 1 = a cos θ, x 2 = b sin θin the case of remote loading S 0 under the assumptions of pure anti plane shear and in the absence of any eigenstrain inside the inclusion. By changing the values of the parameters a and b we can consider elliptic inclusions of different sizes and aspect ratios.…”
mentioning
confidence: 99%
“…This can define the existence of mechanical imperfections, interfacial damages (such as debonding, delamination, sliding, and/or cracking across the interface), thermic isolations, chemical reactions, and so forth. In Videla and Atroshchenko [35], the problem of homogeneously imperfect interface reported by Achenbach and Zhu [36] and Hashin [37,38] is generalized to micropolar elastic media assuming that couple tractions are continuous across the interface and proportional to the jumps of the out-of-plane microrotation. The simulation of the mechanical effects on microstructured Cosserat materials reinforced by inclusions with perfect and imperfect interfaces is developed using the boundary element method in Atroshchenko et al [39].…”
Section: Introductionmentioning
confidence: 99%
“…The current work considers an embedded multi-coated elliptic nano-fiber under three different interfacial conditions of pure sliding (completely damaged), imperfect (partially damaged), and perfect (undamaged) in anti-plane couple stress theory. To model interfacial damage in this framework, in addition to what is considered in traditional theory, the couple traction is allowed to be continuous while the components of the microrotation vector are considered to be proportional to the related couple traction along the interfaces; see, for example, Atroshchenko et al (2017), Hashemian et al (2015), Shodja and Hashemian (2019), and Videla and Atroshchenko (2017).…”
Section: Introductionmentioning
confidence: 99%